Comparison between Taguchi Method and Response Surface Methodology (RSM) in modelling CO2 laser machining - Subramonian, Sivarao; Abdul Rahim, Samsudin (JJMIE, 2014)
The applications of Taguchi method and RSM to modelling the laser parameters when machining industrial PVC foams is presented. The influence of cutting speed, laser power, frequency, duty cycle, and gas pressure on kerf width has been considered in this investigation according to Taguchi method using a standard orthogonal array L27 and RSM using a central composite design. Taguchi technique as well as 3D surface plot of RSM revealed that the cutting speed is the most significant factor in minimizing kerf width followed by laser power and etc. A predictive mathematical model was then developed through a regression analysis in both analytical tools to study the response. Though both the techniques predicted near values of average error, the RSM technique seems to be more promising in predicting the response via mathematical modelling over the Taguchi technique.